Correlated network activity enhances synaptic efficacy via BDNF and the ERK pathway at immature CA3–CA1 connections in the hippocampus - Mohajerani, Majid H. (National Academy of Sciences, 2007)
At early developmental stages, correlated neuronal activity is thought to exert a critical control on functional and structural refinement of synaptic connections. In the hippocampus, between postnatal day 2 (P2) and P6, network-driven giant depolarizing potentials (GDPs) are generated by the synergistic action of glutamate and GABA, which is depolarizing and excitatory. Here the rising phase of GDPs was used to trigger Schaffer collateral stimulation in such a way that synchronized network activity was coincident with presynaptic activation of afferent input. This procedure produced a persistent increase in spontaneous and evoked α-amino-3-hydroxy-5-methyl-4-isoxadepropionic acid-mediated glutamatergic currents, an effect that required calcium influx through postsynaptic L-type calcium channels. No potentiation was observed when a delay of 3 sec was introduced between GDPs and afferent stimulation. Pairing-induced potentiation was prevented by scavengers of endogenous BDNF or tropomyosin-related kinase receptor B (TrkB) receptor antagonists. Blocking TrkB receptors in the postsynaptic cell did not prevent the effects of pairing, suggesting that BDNF, possibly secreted from the postsynaptic cell during GDPs, acts on TrkB receptors localized on presynaptic neurons. Application of exogenous BDNF mimicked the effects of pairing on synaptic transmission. In addition, pairing-induced synaptic potentiation was blocked by ERK inhibitors, suggesting that BDNF activates the MAPK/ERK cascade, which may lead to transcriptional regulation and new protein synthesis in the postsynaptic neuron. These results support the hypothesis that, during a critical period of postnatal development, GABA(A)-mediated GDPs are instrumental in tuning excitatory synaptic connections and provide insights into the molecular mechanisms involved in this process.